2016
DOI: 10.1159/000452149
|View full text |Cite
|
Sign up to set email alerts
|

Early Carotid Artery Stenting for Cerebral Watershed Infarction Is Safe and Effective: A Retrospective Study

Abstract: Background: With carotid artery stenosis, infarcts can occur in the cortical or internal watershed areas, or both. The timing of carotid artery stenting (CAS) after a cerebral watershed infarction (CWI) is not yet codified. In this retrospective study, we analyzed the safety and clinical effect of early CAS for CWI patients due to carotid artery stenosis. Methods: Between March 2011 and April 2014, 120 CWI patients with ipsilateral carotid artery stenosis were recruited. Of these 120 patients, 63 received CAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Therefore, early endovascular treatment combined with dual antiplatelets may reduce the recurrent risk for WS infarction patients with large cerebral artery stenosis. A retrospective study reported that early carotid artery stenting for WS infarction was safe and could improve the functional outcome .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early endovascular treatment combined with dual antiplatelets may reduce the recurrent risk for WS infarction patients with large cerebral artery stenosis. A retrospective study reported that early carotid artery stenting for WS infarction was safe and could improve the functional outcome .…”
Section: Discussionmentioning
confidence: 99%